Extraction of bioactive compound from Star Anise (Illicium Verum) using soxhlet extraction: artcle / Nurulfarhana Mat Amin and Dr NorHuda Ismail - Mat Amin, Nurulfarhana; Ismail, NorHuda (2017)
To date, people around the world are demanding natural constituents in food and pharmaceutical product due to its medical value within the plant such as antimicrobial and antifungal properties. Star anise or Illicium verum is star shaped fruit which normally used as a flavor in cooking and also as healing herbs where its shows medicinal properties that serve notable health benefits. In this research, Illicium verum is used to study the highest oil content in it by using three different solvents, to determine its major phytochemical compound by using GCMS and to identify its chemical structure by using FTIR. The sample of Illicium verum is prepared and the oil content is obtained using soxhlet extraction method. Solvents used in this research are distilled water, methanol and ethanol where the ratio of solvent to sample is 10 : 1. The essential oil obtained from the extaction is characterized using GCMS to determine its chemical compound and FTIR to determine its chemical structure. Methanol acts as the best solvent since it extracts the highest amount of oil from illicium verum. From GCMS, estragole which has antimicrobial, antispasmodic, antioxidant antivities is detected as the major compound found in the illicum verum in both methanol and ethanol solvent while from FTIR analysis, chemical compound presence in the extracted oil are hydroxyl group, alkyl halides, carboxylic acid, alkanes and aldehydes.